2021
DOI: 10.1002/jcla.24032
|View full text |Cite
|
Sign up to set email alerts
|

miR‐3146 induces neutrophil extracellular traps to aggravate gout flare

Abstract: Background Gout is an inflammatory arthritis and is characterized by the accumulation of deposited monosodium urate (MSU) crystals in the joints. miRNAs may act as key regulators of gout pathogenesis. The aim of our study was to explore the underlying role and molecular mechanism of miR‐3146 in the formation of neutrophil extracellular traps (NETs) during the pathogenesis of gout. Methods The expression of miR‐3146 and sirtuin 1 (SIRT1) was determined by real‐time reverse transcription‐polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Recently, it has been shown that MSU stimulation can significantly increase miR-3146 expression in neutrophils, accompanied by the formation of many NETs. In contrast, treating rats with antagomir-3146 reduced NETs formation and relief of joint swelling and inflammation, suggesting that early NETs formation exacerbates GA and that miR-3146 plays a role vital role before NETs formation ( 83 ). However, the current research on NETs is still inadequate, and how miRNAs regulate the development of NETs in gout is still unclear.…”
Section: The Function and Mechanism Of Mirnas In Gamentioning
confidence: 99%
“…Recently, it has been shown that MSU stimulation can significantly increase miR-3146 expression in neutrophils, accompanied by the formation of many NETs. In contrast, treating rats with antagomir-3146 reduced NETs formation and relief of joint swelling and inflammation, suggesting that early NETs formation exacerbates GA and that miR-3146 plays a role vital role before NETs formation ( 83 ). However, the current research on NETs is still inadequate, and how miRNAs regulate the development of NETs in gout is still unclear.…”
Section: The Function and Mechanism Of Mirnas In Gamentioning
confidence: 99%
“…5A, and Additional file 1: Supplementary Text). [44][45][46][47][48][49] In contrast, five genes (MIR3146, ESRRA, SEC23IP, DIP2C, and CPD(SLC6A4)) were directly related to serotonin and GABA neurotransmitters, which are known to be relevant to mood disorders like depression and anxiety (Fig. 5B, and Additional file 1: Supplementary Text).…”
Section: The Interpretation Of Eleven Genes Associated With 17 Methyl...mentioning
confidence: 99%
“…5B, and Additional file 1: Supplementary Text). [44,45,[50][51][52][53][54][55][56][57][58][59][60][61][62] It's important to note that previous studies have demonstrated the impact of psychological stress on apoptosis in immune cells within the bloodstream. [63][64][65][66][67][68] This study, through the identification of differential methylation in genes associated with cell stress response, regulation of mitochondrial function, and control of apoptosis in individuals with anxiety disorders, provides support for these previous findings (Fig.…”
Section: The Interpretation Of Eleven Genes Associated With 17 Methyl...mentioning
confidence: 99%
“…To date, ten miRNAs (miR-15b-5p ( 100 ), miR-142-3p ( 101 ), miR-144 ( 102 ), miR-146a-5p ( 103 ), miR-155 ( 104 ), mir-223 ( 105 ), miR-378a-3p ( 100 ), miR-505 ( 106 ), miR-3146 ( 107 ), and miR-4512 ( 108 )) have been shown to regulate NETosis in mammals ( 109 ). Three of them are considered inflamma-miRs (miR-146a-5p, miR-155, and miR-223) in the present review and will be briefly described.…”
Section: Inflammatory Mirnas As Regulators Of Neutrophil Extracellula...mentioning
confidence: 99%